2016
DOI: 10.1002/qua.25324
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐orbit ab initio and density functional theory investigation of bismuth monoboronyl, BiBO

Abstract: The molecular properties of bismuth monoboronyl, BiBO, were investigated using high‐level ab initio and density functional theory calculations by including the effect of spin‐orbit coupling (SOC). SOC does not cause any change in the BiB bond length of BiBO, by contrast it causes significant elongation of the BiB bond of BiBO−, by ∼0.03 Å. The BiB bond length of BiBO− that is calculated by considering SOC is almost identical to that of BiBO; this result is consistent with a recent experimental study. The te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…[20] We chose an active space with 4 Σ g − , and 2 Σ g − excited states were included in the SA8-CASSCF(13,10) calculations, both followed by multireference configuration interaction (MRCI) calculations to account for the dynamic electron correlation effect. [21] As shown previously for BiBO, [17] spin-orbit (SO)…”
supporting
confidence: 62%
See 1 more Smart Citation
“…[20] We chose an active space with 4 Σ g − , and 2 Σ g − excited states were included in the SA8-CASSCF(13,10) calculations, both followed by multireference configuration interaction (MRCI) calculations to account for the dynamic electron correlation effect. [21] As shown previously for BiBO, [17] spin-orbit (SO)…”
supporting
confidence: 62%
“…[16] A recent PES and theoretical study on the BiBO − species showed that it contains a Bi−B single bond and a B≡O triple bond, [10] which is confirmed subsequently by a high level ab initio calculation. [17] In the current article, we The experiment was carried out using a magnetic-bottle PES apparatus equipped with a laser vaporization supersonic cluster source, details of which have been published elsewhere. [2,18] The BiB 2 O − and Bi 2 B − cluster anions were produced by laser vaporization of a Bi/ 11 B mixed target, which was used to produce small bare boron clusters (B n − ).…”
mentioning
confidence: 99%
“…There is only one recent computational study, which considered a Bi−B triple bond stabilized by bulky ligands as RB≡BiR . A recent PES and theoretical study on the BiBO − species showed that it contains a Bi−B single bond and a B≡O triple bond, which is confirmed subsequently by a high‐level ab initio calculation . In the current article, we report the first observation of Bi≡B triple bonding and Bi=B double bonding in two clusters, BiB 2 O − ([Bi≡B−B≡O] − ) and Bi 2 B − ([Bi=B=Bi] − ) using a joint PES and theoretical study.…”
Section: Figuresupporting
confidence: 53%
“…While the 2 Π g ground state was calculated alone at the SA2‐CASSCF(13,10) level, the 4 Π u , 2 Π u , 4 Σ u − , 2 Σ u − , 4 Σ g − , and 2 Σ g − excited states were included in the SA8‐CASSCF(13,10) calculations, both followed by multi‐reference configuration interaction (MRCI) calculations to account for the dynamic electron correlation effect . As shown previously for BiBO, spin–orbit (SO) coupling is expected to be important for BiB 2 O and Bi 2 B, as well. We carried out the SO coupling calculations using the state‐interaction method based on the MRCI wavefunctions (MRCI+SO) .…”
Section: Figurementioning
confidence: 99%